2010
DOI: 10.1007/12_2010_51
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electric Fields on Block Copolymer Nanostructures

Abstract: In this chapter we overview electric-field-induced effects on block copolymer microdomains. First, we will consider the thin film behavior and elucidate the parameters governing electric-field-induced alignment. We describe the structural evolution of the alignment in an electric field via quasi in situ scanning force microscopy (SFM) using a newly developed SFM setup that allows solvent vapor treatment in the presence of high electric fields. Second, we will turn to bulk structures and show novel effects of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 71 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…3,4 It has been shown that by changing temperature [7][8][9] or by applying external fields such as shear flow [10][11][12][13][14][15] or electric fields [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] phase transitions between different ordered structures can be induced. Electric fields have been shown as an effective method of controlling the orientation of the structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 It has been shown that by changing temperature [7][8][9] or by applying external fields such as shear flow [10][11][12][13][14][15] or electric fields [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] phase transitions between different ordered structures can be induced. Electric fields have been shown as an effective method of controlling the orientation of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…Electric fields have been shown as an effective method of controlling the orientation of the structures. [25][26][27][28] It has been shown that for lamellae and cylindrical systems there is a preferred orientation of the grains with respect to the electric field. [28][29][30][31][32] Experimental work by Böker et al, 28 describes various microscopic mechanisms of lamellae alignment parallel to an applied electric field.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The cooperative motions of LC units within the aligned materials lead to macroscopic deformations. [18][19][20][21][22] Herein, the dynamic reorientation process of an MPS mesostructure was pursued under application of external electric fields [21,22] using in situ scanning probe microscopy and synchrotron X-ray scattering measurements. [8,9] Despite the accumulated knowledge concerning the previously discussed light-driven materials, photoresponsive systems that have an intermediate "mesoscopic" feature size (typically 10-100 nm) remain an underexplored area.…”
mentioning
confidence: 99%
“…[17] Only a few attempts have been made to alter the MPS structure by external stimuli. [18][19][20][21][22] Herein, the dynamic reorientation process of an MPS mesostructure was pursued under application of external electric fields [21,22] using in situ scanning probe microscopy and synchrotron X-ray scattering measurements. The elucidation of the light-induced reorientation processes of the MPS morphology of a block copolymer remains a challenging problem.…”
mentioning
confidence: 99%
“…The effects of electric field on the self-assembly of block copolymer thin films receives appreciable attention recently. [9][10] Previous studies showed that external electric field not only accelerated the selfassembly process, but it could be employed to modify micro-structures from the intrinsic morphology of self-assembly. The objectives of this study are to (1) investigate the effect of external electric field on the self-assembly of PS-b-P2VP thin films, (2) demonstrate an e-field method for modulating photonic band-gaps of the lamellar structure, and (3) provide a controlled way to form lamellar photonic crystals on a 2-dimemsional film surface.…”
Section: Effects Of Electric Fieldsmentioning
confidence: 99%